P300 Investigation of the association between infantile skin conditions and the main dietary factors: a national cohort study. (June 2019) - Quinn, Shauna; Zgaga, Lina; Taut, Cristina
Abstract : Aims: Skin conditions are common amongst infants. A topic of particular interest is whether or not eczema is associated with the main dietary factors of the infant within the first nine months. The dietary factors investigated are breastfeeding duration, artificial formula feeding, timing of introduction of formula and solids. Data was acquired from the Growing Up in Ireland: National Longitudinal Study, following the progression of two cohorts of children aged 9 years and 9 months. The aim of this study is to investigate the association between skin conditions and the main dietary factors in a sample of 9- month old infants. Methods: The study population (9, 326 infants) examined was Wave 1 of the infant cohort of Growing Up in Ireland. Large numbers of covariates were investigated, as a result of existing literature. Chi-square tests were performed for analyses of the association between diagnosed skin conditions and the categorical variables chosen. T-tests of differences in the mean and 95% CI's estimation were employed for all continuous variables. During the analysis, skin conditions were characterised as a binary variable. All variables were considered in the multivariable logistic regression model, excluding insignificant variables from the final model. Results: Introduction of artificial formula was found to have a positive association with diagnosed skin conditions in the infant (OR=0.999, 95%CI: 0.997–1, p-value=0.02226). Earlier introduction led to a higher risk of skin conditions. Breastfeeding duration and introduction of solids were not associated with neonatal skin conditions. Maternal stress (OR= 1.01, 95%CI: 1.00–1.02, P-values= 0.05) and smoking in the household during pregnancy (OR=0.90, 95%CI: 0.82–0.98, P-value= .02) have suggestive associations with skin conditions. Conclusion: Early introduction of artificial formula has a positive association with skin conditions in infants, while breastfeeding duration and introduction of solids may have no correlation. This study highlights the importance of the WHO recommendation of exclusive breastfeeding for 6 months.